Esplenectomía en los niños. Resultados en el Hospital Infantil Docente "William Soler" - Hernández Amador, Guillermo; Rodríguez García, Manuel; Morandeyra Martín, Ángel; Rodríguez García, Manuel; Vilorio Barrera, Pedro; de la Torre Montejo, Ernesto; Guerchicoff de Svarch, Eva (Revista Cubana de Pediatría, 2023)
Revisión de esplenectomías durante 7 años.